Tannin-furfuryl alcohol adhesive for particleboard - Rosli, Hafiz Hafizi (2016)
Acacia (Acacia mangium) is a fast growing species that dominate the plantation in Malaysia that have potential to partially replace phenol. Thus, with the fast maturing Acacia plantation in this country, there is urgency to find the best way to utilize this timber resource. Polyphenolic structure that contain in A. mangium tannin, has potential to be used as a good bonding agent. In this study, the tannin solution with 30%± solid content was extracted from Acacia bark. The aim of this study was to determine the physical and mechanical properties of the particleboard made from Tannin-furfuryl alcohol (TFA). The tannin was mixed with furfuryl alcohol (FA) at two ratio of tannin and PF (4:1 and 3:1) were used as variable with fixed value at pH 10. Then, a duplicate of laboratory particleboards were made by using Urea Formaldehyde (UF) and TFA resin as a binder. The physical and mechanical properties of particleboard were tested according to EN 312 1995 and BS EN 317 1993 for modulus of rupture, modulus of elasticity, internal bonding test, thickness swelling and water absorption respectively. The result shows that the IB strength for particleboard from TFA 4:1 and 3:1 were 0.34 and 0.25 N/mm2, respectively. While the particleboard from UF resin was 0.47 N/mm2.